2002
DOI: 10.1063/1.1435075
|View full text |Cite
|
Sign up to set email alerts
|

Bonding nature of rare-earth-containing lead-free solders

Abstract: The ability of rare-earth-containing lead-free solders to wet and bond to silica was investigated. Small additions of Lu (0.5–2 wt. %) added to eutectic Sn–Ag or Au–Sn solder render it directly solderable to a silicon oxide surface. The bonding is attributed to the migration of the rare-earth element to the solder–silica interface for chemical reaction and the creation of an interfacial layer that contains a rare-earth oxide. It was found that additions of rare-earth materials did not significantly modify the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(28 citation statements)
references
References 8 publications
1
27
0
Order By: Relevance
“…The reasons for this may be related to the fact that RE elements have a stronger affinity for oxygen than most metals and tend to reduce metal oxides via the formation of RE oxides. [26][27][28] That is, RE elements can promote chemical reactions at the interface and provide very strong bonding during soldering. 18 Other investigators consider that RE elements are adsorbed at the grain boundaries of the IMC second phase and change the relative relationship of the growth velocities between the crystalline directions of the polycrystalline IMC, which reduces the size of the IMC particles and distributes the IMCs more uniformly.…”
Section: Microstructure At the Solder/cu Substrate Interfacementioning
confidence: 99%
“…The reasons for this may be related to the fact that RE elements have a stronger affinity for oxygen than most metals and tend to reduce metal oxides via the formation of RE oxides. [26][27][28] That is, RE elements can promote chemical reactions at the interface and provide very strong bonding during soldering. 18 Other investigators consider that RE elements are adsorbed at the grain boundaries of the IMC second phase and change the relative relationship of the growth velocities between the crystalline directions of the polycrystalline IMC, which reduces the size of the IMC particles and distributes the IMCs more uniformly.…”
Section: Microstructure At the Solder/cu Substrate Interfacementioning
confidence: 99%
“…[6][7][8][9] Preliminary studies on RE-containing solders, such as Sn-0.7Cu, Sn-Zn, Sn-Ag-Cu, Sn-3.5Ag, and Au-Sn, show a discrepancy in reported microstructures and mechanical properties. [10][11][12][13][14][15][16][17][18] For example, a study on Sn-Ag-Cu alloys with 0.1 and 0.25 wt.%Ce and La additions 12 reported RE-containing intermetallics in the microstructure, while another showed no evidence of discrete intermetallics being formed. 13 Furthermore, there is little evidence in the literature for the formation of homogeneous microstructures in these RE solders.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies report that RE additions increase the strength of Sn-Ag-Cu solders, with an accompanying decrease in strain to failure. 10,11,13,14,[16][17][18] Other studies, however, have reported increases in strain to failure with small amounts of RE. Chen et al, 12,15 for example, observed both an increase in tensile strength and elongation of Sn-Ag-Cu with RE additions up to 0.05 wt.% (a mixture of Ce and La).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Several authors have shown that the addition of small amounts of RE elements can decrease alloy melting temperature, 2,8,14 improve wettability, 2,5,9,16 and even promote strong bonding to semiconductors such as silicon. 1,13 Rare earths have also been shown to refine the solder microstructure by decreasing the Sn grain size, 2,9,10,17 and intermetallic particle size, 2,9,15,17 and decrease the Cu 6 Sn 5 layer that forms between the Cu substrate and the Pb-free solder. 14,15 The mechanical response of these materials is dependent on the type of RE elements, and their concentration and morphology.…”
Section: Introductionmentioning
confidence: 99%